(untitled) (Fiep Bulletin - online, 2016)
The objective of this paper is to discuss body nowadays and its relationship with the consumer and media. If previously the subjects consumed to meet their basic needs, in contemporary society, consumption is synonymous of self-fulfillment, pleasure and happiness. By consuming, the goal is to acquire artifacts that enable the transformation of a common body in a beautiful and perfect one. And the image of this perfect body is propagated by the media, so that consumers find themselves encouraged to consume products that enable them to achieve this standard. In this sense, the body is also a product to be consumed, modeled and transformed according to the wishes of humans and market demands. As a social construct, body must be understood as a cultural event, full of signs, meanings and senses and remains in constant transformation, through the experiences and learning that happen constantly.